The Influence of Digital Marketing and Online Customer Reviews on Clothing Sales - Hanif, Hanif; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (IJBLE Scientific Publications Community Inc., 2025)
This research aims to find out (1) whether digital marketing has an effect on clothing sales at Tanah Abang Market Block A, Floor 6, Central Jakarta, (2) whether online customer reviews have an effect on clothing sales at Tanah Abang Market, Block A, Floor 6, Central Jakarta, and ( 3) Does digital marketing and online customer reviews have an influence on clothing sales at Tanah Abang Market, Block A, Floor 6, Central Jakarta. The method used in this research is quantitative with a survey approach. The population in this study were clothing shop owners at Tanah Abang Market, Block A, Floor 6, Central Jakarta, totaling 200 shop owners with a sample size of 186 based on the proportional random sampling technique using the Isac Michael table. The results of the research show that digital marketing and online customer reviews together have a significant influence on clothing sales at Tanah Abang Market, Block A, Floor 6, Central Jakarta, as shown by the results of the R Square coefficient of determination test of 0.960, so it can be concluded that 96% of digital marketing and online customer reviews can influence clothing sales together.